Shoulder pain in elite swimmers - Sein, M. L. (2006)
Shoulder pain in elite swimmers is common and its cause is unknown. One hypothesis is that repetitive swimming leads to shoulder laxity, which in turn leads to impingement and shoulder pain. An observational cross-sectional study was designed to test this hypothesis. Eighty elite swimmers (13-25 years of age) completed questionnaires on their swimming training, pain and shoulder function. They were given a standardized clinical shoulder examination, and tested for inferior glenohumeral joint laxity using a noninvasive electronic laxometer designed for this study. Fifty-two swimmers also attended for a shoulder MRI. The laxometer had good-excellent reliability for inter-observer (Intra-class correlation coefficient, ICC = 0.74) and intra-observer (ICC = 0.76) assessments of joint laxity. The reliability of MRI-determined supraspinatus tendinosis was excellent with a single experienced musculoskeletal radiologist (intra-observer ICC = 0.85) and fair for an inter-observer assessment including less experienced radiologists (ICC = 0.55). MRIdetermined supraspinatus tendinosis was present in 36/52 (69%) swimmers, including four international-level athletes. A positive impingement sign correlated with supraspinatus tendinosis (r = 0.49, p = 0.0002). The impingement sign had 100% sensitivity and 65% specificity for diagnosing supraspinatus tendinopathy. Shoulder laxity correlated modestly with impingement (r = 0.23, p < 0.05). There was no association between shoulder laxity and supraspinatus tendinosis (r = 0.24, p = 0.08). The number of hours swum/week (r = 0.36, p = 0.01) and the weekly mileage (r = 0.34, p = 0.02) both correlated significantly with supraspinatus tendinopathy whereas swimming stroke preference did not. Multiple logistic regression analysis performed with supraspinatus tendinopathy as the dependent variable showed the combination of hours swum/week and weekly mileage correctly predicted tendinopathy in 85% of elite swimmers. These data indicate that: (1) supraspinatus tendinopathy is a major cause of shoulder pain in elite swimmers; and (2) this supraspinatus tendinopathy is induced by the volume/dose of swimming; and (3) shoulder laxity per se has only a minimal association with shoulder impingement in elite swimmers. These finding in humans are consistent with animal and tissue culture findings which support the hypothesis that tendinopathy is related to the dose and duration of load to tendon cells.